2013
DOI: 10.1097/ncc.0b013e31826c7af2
|View full text |Cite
|
Sign up to set email alerts
|

Hope Pictured in Drawings by Women Newly Diagnosed With Gynecologic Cancer

Abstract: The use of drawings in clinical situations might give cancer nurses new perceptions of hope and other phenomena. Patients might feel threat and despair when diagnosed with cancer; they need gentle truth about reality, and they long for being together with loved ones. Nurses are in a unique position to enable hope in this situation through listening and active engagement. Drawing might be a tool in understanding the hope. Drawings picture where words come short.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Whilst temporal breadth is important, research is diffused over a range of time points, with much occurring well after original diagnosis. There is little research that takes place within 6 months of diagnosis (e.g., Ekwall, Ternestedt, & Sorbe, 2003; Hammer, Hall, & Mogensen, 2013; Hammer et al, 2009). One particular gap in the time frame is that where women have completed active treatment but are not yet officially in remission from cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst temporal breadth is important, research is diffused over a range of time points, with much occurring well after original diagnosis. There is little research that takes place within 6 months of diagnosis (e.g., Ekwall, Ternestedt, & Sorbe, 2003; Hammer, Hall, & Mogensen, 2013; Hammer et al, 2009). One particular gap in the time frame is that where women have completed active treatment but are not yet officially in remission from cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, qualitative research has expanded to explore the experience of cancer, particularly in relation to topics such as hope (Hammer et al, 2013; Reb, 2007), meaning (Akyüz, Güvenç, Üstünsöz, & Kaya, 2008; Roberts & Clarke, 2009; Sekse et al, 2010), the impact of childlessness or loss of fertility for younger women (Molassiotis et al, 2002; Roberts & Clarke, 2009) and changing family roles (Akyüz et al, 2008). Other topics identified included uncertainty and risk (Roberts & Clarke, 2009; Sekse et al, 2010), body image and sexual function (Ekwall et al, 2003; Maughan, Heyman, & Matthews, 2002; Molassiotis et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Seventeen studies utilized theoretical frameworks, including: the common-sense model of self-regulation,23–30 phenomenology,31–34 phenomenography,35,36 a feminist framework,3739 the illness-meaning model,40–42 the social representation theory,43,44 and the transition theory 45,46. Theoretical frameworks underpinning the studies were not reported in the remaining fifteen publications 4761…”
Section: Resultsmentioning
confidence: 99%
“…For studies where drawing was used together with interviews, drawings were often made after a one-on-one interview with a researcher and a discussion about the image followed. Two studies specified that participants were alone when completing the drawing task in interviews 31,33. Conversely, in another study drawings were created in a group setting with other participants 32…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation